The burnout dimension emotional exhaustion and impairment of work participation: A prospective study of 2308 employees subject to social security contributions in Germany - Rose, Uwe; Buchallik, Friederike; Burr, Hermann; Kersten, Norbert (Gesundheitswesen (Bundesverband der Ärzte des Öffentlichen Gesundheitsdienstes (Germany)), 2025)
The present study examines the relationship between the burnout dimension emotional exhaustion and subsequent events of work nonparticipation (long-term sickness absence, unemployment, early retirement) and their duration.The data basis was the Study on Mental Health at Work (S-MGA); a follow-up study based on a random sample of n=4511 employees subject to social security contributions aged 31-60 years at baseline and their follow-up after 5 years (n=2460). Burnout symptoms were measured at the time of the baseline survey by means of a questionnaire, while the employment and sickness absence history was recorded at follow-up by means of an interview. Associations between the burnout scale at T1 and subsequent events of inactivity were analysed using a two-part model: i. e., events were predicted using logistic regression, and their duration was predicted using generalised linear regression models (GLM).The burnout scale was associated with the events and duration of long-term sickness absence; among men with an odds ratio [OR]=1.72 (95% CI=1.31; 2.27) and among women with an OR=2.23 (95% CI=1.73; 2.88) per scale point for the occurrence of an event. Among those who experienced long-term sickness absence, the duration (in months) increased by a factor of Exp(β)=1.44 (95% CI=1.23; 1.69) for men and Exp(β)=1.29 (95% CI=1.09; 1.52) for women for each scale point on the burnout scale.From a clinical and health economic point of view, it is a relevant finding that the burnout dimension of emotional exhaustion is associated with events and duration of work nonparticipation.